Exploring Students’ Affective on Using Asynchronous Learning During the Pandemic Period - Yudha Andana Prawira; Vidia Lantari Ayundhari; Titim Kurnia (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
The distance learning can greatly improve student’s cognitive development, but its success in increasing students' affective competence have not been conclusively reported. This study aims to investigate students’ affective aspects, parents, and teacher perspective on islamic religious education using asynchronous learning. Data were collected using questionnaires, interview, and observation. The data were analysed using descriptive analysis. The results show that there was a change on students’ competence in terms of affective religious aspects. Initially 60% students have negative attitudes and decreased to 30% after they had experienced asynchronous distance learning with commitment of learning establishment. The parents in their interview expressed that they were greatly assisted by the commitment of learning their children formed. The asynchronous learning with learning commitment can be considered successful to help students improve their attitudes. This study shows that e-learning accompanied by a learning commitment between student and teachers turns out to be able to give positive results on the part of students' affective on islamic religious education.